2001
DOI: 10.1524/zkri.216.8.442.20353
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of kristiansenite: a case of class IIB twinning by metric merohedry

Abstract: The structure of the new disilicate kristiansenite, Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 15 publications
5
29
0
Order By: Relevance
“…which is in good agreement with the previously reported formula (Ferraris et al, 2000;Khomyakov et al, 2001 In accordance with others members of LGM, the structure of labuntsovite-Fe consists of undulated chains (rods) formed by M1Ø 6 -and ] 2 }. The distortion of octahedral chains results in the deformation of the siliconoxygen rings.…”
Section: Peculiarity Of Labuntsovite-fe Structuresupporting
confidence: 92%
See 1 more Smart Citation
“…which is in good agreement with the previously reported formula (Ferraris et al, 2000;Khomyakov et al, 2001 In accordance with others members of LGM, the structure of labuntsovite-Fe consists of undulated chains (rods) formed by M1Ø 6 -and ] 2 }. The distortion of octahedral chains results in the deformation of the siliconoxygen rings.…”
Section: Peculiarity Of Labuntsovite-fe Structuresupporting
confidence: 92%
“…In disordered LGM (space group Cm) the sites A, B and C are split into numerous subsites with low occupancy factors. Labuntsovite-Fe, the Fe-dominant member of the labuntsovite group, was first discovered in the Khibiny alkaline massif on Mt Kukisvumchorr (Ferraris et al, 2000;Khomyakov et al, 2001). The unit-cell parameters of the holotype sample are: a = 14.249 (6), b = 13.791 (6), c = 7.777 (2) Å , = 116.82 ; space group C2/m.…”
Section: Introductionmentioning
confidence: 99%
“…The structure was solved by direct methods [30] in the monoclinic space group C2/c, as indicated by experiment, using neutral atom scattering factors, and refined to an R 1 index of 6.45% with anisotropic displacement parameters. However, in their original description of kristiansenite, Ferraris et al [6] found that the crystals of kristiansenite typically show metric merohedral twinning. While the underlying structure including cation ordering is triclinic, the twin law belonging to the higher Laue group makes the structure appear monoclinic within experimental error.…”
Section: Crystal Structure Refinementmentioning
confidence: 99%
“…The position of Ca1 was fixed arbitrarily as the origin. Following [6], the structure was refined to an R 1 index of 4.96% in the unconventional triclinic space group setting C1.…”
Section: Crystal Structure Refinementmentioning
confidence: 99%
See 1 more Smart Citation